Effects of grape seedlings intercropping with post-grafting generation of two floricultural accumulator plants on soil enzymes activity under cadmium stress. Issue 4 (February 2019) - Wu, Caifang; Liu, Ji; Xia, Dan; Yang, Liu; Sun, Jing; Lin, Lijin
Abstract: Pot experiments were conducted to study the effects of grape seedlings intercropping with post-grafting generation of Cosmos sulphureus and Impatiens balsamina on soil enzymes activity under cadmium (Cd) stress. The result showed that: under Cd stress, grape intercropping with the post-grafting generation of C. sulphureus had significant effect, and grape intercropping with the generation of ungrafted C. sulphureus (C.CK) significantly increased soil catalase, soil urease and soil invertase activity compared to grape monoculture (MG). Grape intercropping with the post-grafting generation of self-rooted grafting by two uniform plant seedlings of I. balsamina (I.UG), the generation of ungrafted I. balsamina (I.CK) and the post-grafting generation of self-rooted grafting by the same one seedling of I. balsamina (I.SG) also significantly increased thses three enzymes activity compared to MG. Grape intercropping with I.UG was the most, and next were I.CK and I.SG. In conclusion, when grape intercropping with C.CK, I.UG, I.CK and I.SG, respectively, the enzymes activity all significantly increased.